Analisis Semiotika pada Poster Film “The Willoughbys" - Ester Armaylia; Amin Aminudin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
A film poster is more than an ordinary image; it is a visual communication medium representing specific cultures and ideologies. Amidst animated narratives that often glorify the ideal family, the film The Willoughbys (2020) presents a unique satirical approach to themes of imperfect or dysfunctional families. This study addresses a central question: how does the poster, as a primary visual representation, convey a narrative that challenges such norms?. Utilizing Roland Barthes’ semiotic theory—encompassing denotation, connotation, and myth—within a qualitative constructivist paradigm, the research demonstrates the poster's role as a complete narrative text. The findings reveal that the poster systematically constructs a comprehensive narrative through a strategic orchestration of visual signs. Specifically, the premise of family dysfunction is established through compositional separation between the background and foreground. The core conflict is manifested in the visual contrast between rigid, passive parent figures and proactive, dynamic children. Furthermore, the inciting incident is symbolized by a satirical travel brochure representing a rebellion plan. Ultimately, the poster transcends mere character introduction to function as a standalone text that effectively encapsulates the film’s critique of "The Myth of the Ideal Family".